2011
DOI: 10.1371/journal.pone.0023527
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan-Extending Effects of Royal Jelly and Its Related Substances on the Nematode Caenorhabditis elegans

Abstract: BackgroundOne of the most important challenges in the study of aging is to discover compounds with longevity-promoting activities and to unravel their underlying mechanisms. Royal jelly (RJ) has been reported to possess diverse beneficial properties. Furthermore, protease-treated RJ (pRJ) has additional pharmacological activities. Exactly how RJ and pRJ exert these effects and which of their components are responsible for these effects are largely unknown. The evolutionarily conserved mechanisms that control l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
3
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 89 publications
(88 reference statements)
4
73
3
4
Order By: Relevance
“…Because we did not assess life spans in this study, the effect of increased levels of IGF-1 by RJ/pRJ treatment on life span was not clear. However, previous studies reported that RJ/pRJ extended the life span in mice and Caenorhabditis elegans (10,11). Further studies are required to evaluate the effects and mechanisms of RJ/pRJ on life span.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Because we did not assess life spans in this study, the effect of increased levels of IGF-1 by RJ/pRJ treatment on life span was not clear. However, previous studies reported that RJ/pRJ extended the life span in mice and Caenorhabditis elegans (10,11). Further studies are required to evaluate the effects and mechanisms of RJ/pRJ on life span.…”
Section: Discussionmentioning
confidence: 96%
“…Accumulating evidence suggests that RJ is rich in a wide variety of nutrients, including vitamins, minerals, and more than 20 amino acids (9). RJ also has numerous potential pharmacological capacities, such as prolonging the life span (in mice and nematodes) (10,11) and reducing fatigue (12), hypertension (13), and hypercholesterolemia, as well as antioxidant and anti-inflammatory effects (8,(14)(15)(16).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated a wide range of health benefits to humans and model organisms, including vasodilative and hypotensive activities (Tokunaga et al, 2004), antitumor (Tamura et al, 1987), anti-inflammatory (Fujii et al, 1990;Kohno et al, 2004), antibacterial and disinfectant properties (Fujiwara et al, 1990;Shen et al, 2010a), antifatigue activity (Kamakura et al, 2001a), and increasing the average lifespan in mice (Inoue et al, 2003) and nematodes (Honda et al, 2011). Because of its great potential benefits to human health, RJ is widely used as a key component in many commercial products including medicine, dietary supplements, and cosmetics (Kamakura et al, 2001c).…”
Section: Introductionmentioning
confidence: 99%
“…RJ has previously been shown to extend lifespan in mice (Inoue, 2003) and in the nematode Caenorhabditis elegans (Honda et al, 2011). However, the primary factor responsible for this lifespan extension remained elusive.…”
Section: Introductionmentioning
confidence: 99%